Mechanism of Fast Atmospheric Energetic Equilibration Following Radiative Forcing by CO2. (10th November 2017) - Dinh, T.; Fueglistaler, S.
Abstract: In energetic equilibrium, the atmosphere's net radiative divergence ( R ) is balanced by sensible ( S ) and latent ( L ) heat fluxes, i.e., R + S + L = 0 . Radiative forcing from increasing CO2 reduces R, and the surface warming following an increase in CO2 is largely due to the reduction in atmospheric energy demand in S and L, with only a smaller surface radiative budget perturbation. With an idealized General Circulation Model, we show that the fast atmospheric adjustment at fixed surface temperature produces the required decrease in the sum of S and L through changes in the near‐surface temperature and specific humidity. In layers near the surface, the reduced radiative cooling forces a temperature increase that leads to a negative Planck radiative feedback and, because of the reduced surface‐atmosphere temperature difference, also to a reduction in sensible heat flux. In the free troposphere, the reduced radiative cooling leads to a weakening of the tropospheric circulation. Consequently, there is a decrease in the water flux exported from the layers near the surface, and as such in precipitation. By mass conservation, the near‐surface specific humidity increases and surface evaporation decreases until it balances the reduced export flux. Other processes can amplify or dampen the responses in S and L and change the partitioning between these two fluxes, but by themselves do not ensure R + L + S = 0 . Key Points: Radiative forcing from increasing CO2 decreases atmospheric radiative divergence Fast atmospheric energetic re‐equilibration requires responses in sensible and latent heat fluxes Mechanistic equations based on simplified physics explain the sensible and latent heat flux responses in GCM calculations